KEBIJAKAN UNITED NATIONS INTERIM ADMINISTRATION MISSION IN KOSOVO (UNMIK) DALAM MEMULIHKAN KOSOVO PASCA KONFLIK ETNIS (1999-2006) - Rezki Amelya; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research will explain about involvement The United Nations as the organization of world peace has a great responsibility and duty in recovering and managing the condition of Kosovo as usual. Directly, as the result this conflict ended with the ethnics conflict between Albanian and Serbian. The ethnic’s conflict can be existed in Kosovo generally is because of the ethnic cleansing of Albanian in the era of Slobodan Milosevic by nasionalist of Serbian. The UN Secretary-General submits to the Security Council in accordance of Security Council Resolution 1244 to establishing the United Nations Interim Administration Mission in Kosovo (UNMIK) as a mandate. UNMIK is a civil administrative institution under the authority of United Nation was built on June 10, 1999. The Mission is mandated to help ensure conditions for a peaceful and normal life for all inhabitants of Kosovo and advance regional stability in the Western Balkans.The method used is library research where obtained through literature review from journals, books, mini thesis, reports, and internet to explain UNMIK’s planned programs. The writer used the theories in this research are international organization theory and resolution conflict theory.This results of this research indicates that The General Secretary of the United Nations, Boutros Boutros Ghali’s term of the Agenda for Peace which covered peacemaking, peacekeeping, and peacebuilding will be the basis for policy of UNMIK. This agendas are calls upon UNMIK to perform basic civilian administrative functions, promote the establishment of substantial autonomy and self-government in Kosovo, facilitate a political process to determine Kosovo's future status, coordinate humanitarian and disaster relief of all international agencies, support the reconstruction of key infrastructure, maintain civil law and order, promote human rights and assure the safe and unimpeded return of all refugees and displaced persons to their homes in Kosovo.Keywords: Ethnical Conflict, Kosovo, Policy, UNMIK, Agenda for Peace